Strangers she knows [large type] - Dodd, Christina (Dodd, Christina. Cape Charade, 2019)
I have three deadly problems:1. I've seriously offended a maniacal killer.2. I just had a bullet removed from my brain.3. My new daughter is growing up too fast--and she's in the line of fire. Living on an obscure, technology-free island off California means safety from the murderer who hunts Kellen Adams and her new family...or does it? Family time becomes terror-time, and at last, alone, Kellen faces a killer playing a cruel game. Only one can survive, and Kellen knows who must win...and who must die.